Pengembangan E-modul Dasar Listrik dan Elektronika Berbasis Web - Nurlaila Ramadani; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2021)
This research is based on the absence of effective modules, so that learning is still teacher-centered and has not yet been created for students to learn independently. Therefore, teaching materials are needed that support the learning process in utilizing technology, one of which is by using e-modules which are accessed via the web. This study aims to produce a valid and practical e-module in basic electricity and electronics subjects for class X TOI at SMK Negeri 2 Payakumbuh. This study uses a 4-D development model, namely with four stages, namely Define, Design, Develop and Disseminate. The subjects of this research trial were students of class X TOI at SMK Negeri 2 Payakumbuh. Data were collected using a validity and practicality questionnaire in the form of a Likert scale which had been validated by an instrument expert lecturer. Data analysis using percentage techniques. The results of e-module development research on distributing e-module validity questionnaires to three respondents consisting of two Electrical Engineering lecturers of UNP and one teacher of Basic Electrical and Electronics subjects obtained an average percentage result on valid criteria. For distributing e-module practicality questionnaires to respondents two teachers of Basic Electrical and Electronics subjects obtained the average percentage results on very practical criteria and e-module practicality questionnaires to respondents 25 students got the average percentage results on very practical criteria. From the research data described, it shows that the development of e-modules made for Basic Electrical and Electronics subjects has been judged to be valid and practical, so that they can be used as teaching materials in the learning process.